2019
DOI: 10.2147/cmar.s229441
|View full text |Cite
|
Sign up to set email alerts
|

<p>The Cytoplasmic Expression Of CLDN12 Predicts An Unfavorable Prognosis And Promotes Proliferation And Migration Of Osteosarcoma</p>

Abstract: Background: To date, the impact and potential molecular mechanisms of CLDN12 and its association with malignancy in osteosarcoma have not been determined. Materials and methods: In the present study, the expression profiles of CLDN12 in osteosarcoma cell lines and tissues were explored by immunohistochemistry. A fetal osteoblast cell line was transfected with a eukaryotic expression plasmid, and endogenous CLDN12 in osteosarcoma cells were silenced through an RNA interference (RNAi) method. These transfections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Osteosarcoma patients are typically treated with chemotherapy, radiotherapy, and surgery. Although recent clinical studies have shown that adjuvant chemotherapy can improve the survival rate of such patients, the prognosis remains poor (Tian et al, 2019;Wang J. et al, 2019). Therefore, the development of improved management and risk stratification methods, as well as the identification of robust prognostic biomarkers, are of high clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma patients are typically treated with chemotherapy, radiotherapy, and surgery. Although recent clinical studies have shown that adjuvant chemotherapy can improve the survival rate of such patients, the prognosis remains poor (Tian et al, 2019;Wang J. et al, 2019). Therefore, the development of improved management and risk stratification methods, as well as the identification of robust prognostic biomarkers, are of high clinical importance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the same researchers found upregulated expression of claudin-12 in lung squamous cell carcinoma (SqCC) tissues, suggesting the CLDN12 gene as a proto-oncogene in SqCC [ 17 ]. Similarly, Tian et al concluded that cytoplasmic overexpression of claudin-12 promotes the proliferation and migration ability of osteosarcoma cells [ 14 ]. Taking into account the tissue-specific expression of the claudin proteins, Jiang et al [ 21 ] noted that they could be used as prognostic and diagnostic biomarkers, e.g., claudin-1 for colon cancers, claudin-3 for ovarian cancers, claudin-10 for hepatocellular carcinomas, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated expression of claudins has been reported in various cancers, suggesting that they may have an important role in the migration, invasion, and metastasis of cancer cells [ 3 , 13 , 14 , 15 , 16 , 17 ]. More than 90% of cancer-related deaths are due to metastases [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormality in cytokine-cytokine receptor interaction is related to OS genesis and poor prognosis (46,47). Abnormality in tight junction promotes a malignant phenotype of OS cells and causes poor prognosis (48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%